2015
DOI: 10.1186/s12889-015-2486-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dyslipidemia and associated factors among the hypertensive population from rural Northeast China

Abstract: BackgroundOur latest study reported the grim status of hypertension in rural China with the prevalence of hypertension reached 51.1 %. However, we lack the latest data about the prevalence and epidemiological features of dyslipidemia among hypertensive residents in rural China.MethodsA cross-sectional survey was conducted from July 2012 to August 2013 through a cluster multistage sampling to a resident group of 4048 individuals (2152 men, 2896 women) with hypertension, age ≥ 35 years, in the rural Northeast Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 26 publications
6
13
1
Order By: Relevance
“…And our study found that subjects from rural areas had higher values for current drinking, current smoking and hypertension. This result was consistent with a previous report which indicated that current smoking and drinking increase the risk of dyslipidemia [37]. A study in Central India reported a higher dyslipidemia prevalence in rural (74.5%) and urban (68.8%) areas [38].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…And our study found that subjects from rural areas had higher values for current drinking, current smoking and hypertension. This result was consistent with a previous report which indicated that current smoking and drinking increase the risk of dyslipidemia [37]. A study in Central India reported a higher dyslipidemia prevalence in rural (74.5%) and urban (68.8%) areas [38].…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, not only did Cetin et al [43] demonstrate a positive correlation between raised (TC, LDL-C and TG) and hypertension, but they also reported the combined effects of hypertension and dyslipidemia on the greater likelihood of cardiovascular events. Consequently, the risk of acquiring CVD owing to dyslipidemia and hypertension co-existence could be multiplicative [37]. Appropriate management of this comorbidity will remain crucial to minimizing disease complications in the short- and medium-term.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, one more meta-analysis study also suggested the same result above, which reported fewer outcomes in SBP and DBP but more clinical efficacy rates that may lead to a discrepancy [53]. ere were a series of studies for hypertension in China, which suggested that dyslipidemia was one of risk factors of hypertension, and hyperlipidemia was associated with increased risk of hypertension [54][55][56][57]. e main effects of lowering blood lipids of GBE were sourced from flavonoids which could improve blood lipids through antioxidant effect and blood pressure reductions were achieved then [58][59][60][61].…”
Section: Findings and Interpretationsmentioning
confidence: 80%
“…Same has been mentioned by Yu et al in their study in which higher annual income was associated with increased risk of dyslipidemia. 16 Similarly, occupation classes were also significantly associated with dyslipidemia. The above-mentioned nonmodifiable factors play an important role in dyslipidemia.…”
Section: Discussionmentioning
confidence: 98%